Capturing quicksilver : the position, power, and plasticity of Chinese medicine in Singapore - Smith, Arielle A. (Epistemologies of healing, 2018)
"Since the turn of the century Singapore has sustained a reputation for both austere governance and cutting-edge biomedical facilities and research. Seeking to emphasize Singapore's capacity for "modern medicine" and strengthen their burgeoning biopharmaceutical industry, this image has explicitly excluded Chinese medicine - despite its tremendous popularity amongst Singaporeans from all walks of life, and particularly amongst Singapore's ethnic Chinese majority. This book examines the use and practice of Chinese medicine in Singapore, especially in everyday life, and contributes to anthropological debates regarding the post-colonial intersection of knowledge, identity, and governmentality, and to transnational studies of Chinese medicine as a permeable, plural, and fluid practice"--